Analisis Peningkatan Literasi Digital Biologi melalui Penerapan Platform Wayground: (Analysis of Improving Digital Literacy in Biology Through The Implementation of The Wayground Platform) - Rahmadhan, Noviyanti Wahyu; Prastiwi, Muji Sri (BIODIK, 2025)
Digital biology literacy in the Animalia topic is important to investigate because this content requires students to critically access, understand, evaluate, and communicate biology-related information in digital environments amid the abundance of online learning resources. This study aims to analyze the use of the Wayground platform on students’ Biology Digital Literacy skills in the Animalia topic. The instruments used in this study consisted of a test to measure students’ Biology Digital Literacy and a response questionnaire. Data were analyzed using correlation and regression tests. The results indicate that the use of Wayground has a significant effect on improving students’ Biology Digital Literacy skills, with a significance value of 0.000 < 0.05. The indicators of Biology Digital Literacy examined include the ability to access digital information, manage information, evaluate information, and communicate information in biology learning, all of which can be facilitated through the Wayground platform. Interactive features such as review questions, automated feedback, and leaderboards support the enhancement of students’ critical thinking skills and learning motivation. Abstrak. Literasi digital biologi pada materi Animalia penting diteliti karena materi ini menuntut peserta didik untuk mampu mengakses, memahami, mengevaluasi, dan mengomunikasikan informasi biologis berbasis digital secara kritis di tengah melimpahnya sumber belajar daring. Penelitian ini bertujuan untuk menganalisis penggunaan platform Wayground terhadap kemampuan Literasi Digital Biologi peserta didik pada materi Animalia. Instrumen yang digunakan dalam penelitian ini berupa tes untuk mengukur Literasi Digital Biologi peserta didik dan angket respon. Analisis data dilakukan menggunakan uji korelasi dan uji regresi. Hasil penelitian menunjukkan bahwa penggunaan Wayground berpengaruh secara signifikan terhadap peningkatan kemampuan Literasi Digital Biologi, dengan nilai signifikansi sebesar 0,000 < 0,05. Indikator kemampuan Literasi Digital Biologi yang diteliti meliputi kemampuan mengakses informasi digital, mengelola informasi, mengevaluasi informasi, dan mengomunikasikan informasi dalam pembelajaran biologi, yang dapat dicapai melalui pemanfaatan platform Wayground. Fitur-fitur interaktif seperti review question, umpan balik otomatis, dan leaderboard mendukung peningkatan keterampilan berpikir kritis serta motivasi belajar peserta didik.